LINGUISTIC ATTITUDES AND LANGUAGE CHOICES AMONG UNIVERSITY STUDENTS IN A MULTILINGUAL GHANAIAN ACADEMIC ENVIRONMENT - Herzuah, Paul; Hammond, Christiana (Universitas Islam Sumatera Utara (UISU), 2025)
In multilingual environments, language users continuously negotiate their linguistic identities by selecting among available languages to achieve specific communicative purposes. However, such choices are not random; they are shaped by context, domain, and attitudes toward each language. Anchored in Communication Accommodation Theory and Identity Negotiation Theory, this study examines students’ language preferences within the academic setting of a Ghanaian university. Adopting a qualitative research design, data were gathered through focus group discussions (FGDs) to capture students’ linguistic choices and the factors influencing them in both academic and informal contexts. The findings indicate that students’ language choices are driven by attitudinal orientations, situational contexts, and group membership dynamics. Elements such as time, place, interlocutors, and conversation topics significantly influence which language is chosen in a given interaction. The study highlights how multilingual students strategically adjust their linguistic behavior to align with social expectations and identity positioning. These insights have implications for understanding language attitudes and communication practices in multilingual educational and professional settings.